Intraoperative conversion during video-assisted thoracoscopy does not constitute a treatment failure. (16th October 2018) - Fourdrain, Alex; De Dominicis, Florence; Iquille, Jules; Lafitte, Sophie; Merlusca, Geoni; Witte-Pfister, Alejandro; Meynier, Jonathan; Bagan, Patrick; Berna, Pascal
Abstract: OBJECTIVES: Intraoperative conversion may be required during video-assisted thoracoscopic surgery (VATS) for lung cancer. We evaluated the morbidity and mortality rates associated with VATS for anatomical pulmonary resection with conversion to thoracotomy and compared this technique with full VATS and an open thoracotomic approach. METHODS: We performed a retrospective, single-centre study between January 2011 and January 2017 and included 610 consecutive patients having undergone either VATS (with or without intraoperative conversion) or open thoracotomy for anatomical pulmonary resection. Pneumonectomies and angioplastic/bronchoplastic/chest wall resections were excluded. After propensity score adjustment, we assessed the 90-day mortality and determined whether the surgical approach was a risk factor for mortality. RESULTS: Of the 610 patients, 253 patients underwent full VATS, 56 patients underwent VATS + conversion and 301 patients underwent up-front open thoracotomy. Relative to the open thoracotomy group, the VATS + conversion group had a higher incidence of cardiac or respiratory comorbidities and was more likely to have an early-stage tumour. Following adjustment, the 90-day postoperative mortality rate was 5.4% ( n = 3/56) in the VATS + conversion group and 3.7% ( n = 11/301) in the open thoracotomy group ( P = 0.58). Likewise, the morbidity rate was similar in these 2 groups. In a multivariable analysis, the surgical approach was not a risk factor for postoperative mortality. CONCLUSIONS: Following anatomical resection for lung cancer, VATS with conversion and open thoracotomy were associated with similar early postoperative morbidity and mortality rates. When in doubt, VATS should be preferred to thoracotomy; it potentially provides the patient with benefits of a fully VATS-based resection but is not disadvantageous when intraoperative conversion is required.